2023
DOI: 10.3390/agronomy13020550
|View full text |Cite
|
Sign up to set email alerts
|

Plant Growth Promoting Rhizobacteria (PGPR) and Arbuscular Mycorrhizal Fungi Combined Application Reveals Enhanced Soil Fertility and Rice Production

Abstract: Rice (Oryza sativa L.) is an important crop that is grown worldwide to supply the world’s expanding food demand. In the current study, the effects of plant growth-promoting rhizobacteria (PGPR) and Arbuscular mycorrhizal fungi (AMF) on soil fertility and rice growth were explored. Rice plants were inoculated to evaluate how AMF fungi and PGPR affect various aspects of soil and plants, implicating abiotic stress tolerances. The experiment was carried out in a completely randomized design with three replicates u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 59 publications
0
3
0
1
Order By: Relevance
“…3.1). For instance, the interaction of AMF and several bacterial genera including plant growth-promoting rhizobacteria (PGPR) and mycorrhiza helper bacteria (MHB) have been shown to support the health of AMF symbiosis, development of hyphae, germination of spore, colonization of root and the metabolous efficiency of AMF (Chen et al 2023c). Some of the noteworthy interactions between AMF and bacteria include the binding of bacteria to the fungal spore, production of volatiles by bacteria, transfer of chemicals inside the fungal spore by bacteria and disintegration of the fungal cellular wall (Miransari 2011).…”
Section: Introductionmentioning
confidence: 99%
“…3.1). For instance, the interaction of AMF and several bacterial genera including plant growth-promoting rhizobacteria (PGPR) and mycorrhiza helper bacteria (MHB) have been shown to support the health of AMF symbiosis, development of hyphae, germination of spore, colonization of root and the metabolous efficiency of AMF (Chen et al 2023c). Some of the noteworthy interactions between AMF and bacteria include the binding of bacteria to the fungal spore, production of volatiles by bacteria, transfer of chemicals inside the fungal spore by bacteria and disintegration of the fungal cellular wall (Miransari 2011).…”
Section: Introductionmentioning
confidence: 99%
“…There is also an interesting recent publication on combinations of a Bacillus strain with other bacteria including a Pseudomonas strain to promote plant growth [58]. Other work has shown the promise of a combination of bacterial and mycorrhizal fungal applications in enhancing soil fertility and rice production due to enhanced mineral uptake from the soil [59].…”
Section: Halophilic Bacteria With Pgpb Potentialmentioning
confidence: 99%
“…In recent years, the application of genomics metabonomics, genomics transcriptomics, and other related technologies has revealed the growth-promoting mechanism of microorganisms, providing new ideas for the development of microbial agents [15]. In recent years [16], the research has shown that the combination of plant growth-promoting rhizosphere bacteria (PGPR) and arbuscular mycorrhizal fungi (AMF), especially AMF+PGPR5, significantly improves rice growth, and yield, and the absorption of essential elements in rice plants. Microbial fertilizers will become a new direction leading the future development of the fertilizer industry and an inevitable choice for the sustainable development of agriculture in China.…”
Section: Introductionmentioning
confidence: 99%